Rat bone marrow stromal cells and oligonucleotides in pain research - Coronel, Maria Florencia (2010)
In the last years, significant progress has been made in the medical treatment of pain. However, pathological pains, such us neuropathic pain, remain refractory to the currently available analgesics. Therefore, new therapeutic strategies are being evaluated. We have recently shown that both bone marrow stromal cells (MSCs) and the oligonucleotide IMT504 can prevent the development of mechanical and thermal allodynia when they are administered to rats subjected to a sciatic nerve crush. This chapter summarizes the laboratory techniques used to isolate and culture MSCs, administer both MSCs and IMT504, perform the nerve injury and determine mechanical and thermal sensitivities.